2011
DOI: 10.1016/j.ffa.2010.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Codes over Rk, Gray maps and their binary images

Abstract: We introduce codes over an infinite family of rings and describe two Gray maps to binary codes which are shown to be equivalent. The Lee weights for the elements of these rings are described and related to the Hamming weights of their binary image. We describe automorphisms in the binary image corresponding to multiplication by units in the ring and describe the ideals in the ring, using them to define a type for linear codes. Finally, Reed Muller codes are shown as the image of linear codes over these rings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 7 publications
(14 reference statements)
0
28
0
Order By: Relevance
“…It is shown in [8] that the ring R k is a commutative ring with |R k | = 2 (2 k ) . It is also shown that ∀a ∈ R k a 2 = 1 if a is a unit 0 otherwise.…”
Section: The Ring Family R Kmentioning
confidence: 99%
“…It is shown in [8] that the ring R k is a commutative ring with |R k | = 2 (2 k ) . It is also shown that ∀a ∈ R k a 2 = 1 if a is a unit 0 otherwise.…”
Section: The Ring Family R Kmentioning
confidence: 99%
“…2 , where w = uv, was given as R 1 in [12]. Notice that this ring is a member of the family of rings R k studied in [17], [18], and [19]. This family of rings has been shown to be very useful in finding good binary self-dual codes as well as good binary QC codes.…”
Section: Skew Constacylic Codes Over Rmentioning
confidence: 99%
“…In [7], another Gray map equivalent to φ was defined. It is also possible to define another Gray map on the local rings of order 16 with a maximal ideal of size 8.…”
Section: The Rings Of Characteristic 2 Arementioning
confidence: 99%
“…One of the early papers using this was [8] in which binary codes were constructed via a non-linear Gray map from quaternary codes. This work was followed by papers where Gray maps were defined from all of the rings of order 4, see [3], and then to other rings, see [2,7,12]. In general, Gray maps have been a central feature of the study of codes over rings.…”
Section: Introductionmentioning
confidence: 99%